Handling of ‘Kent’ mango destined for the market as a fruit to eat - Osuna-García, Jorge Alberto; Gómez-Jaimes, Rafael; Graciano-Cristóbal, María Josefina (Revista Mexicana de Ciencias Agrícolas, 2022)
The increase in demand for ready-to-eat ripe mango opens up an interesting possibility for mango producers in Mexico due to the geographical proximity of production sites to U.S. markets. The key aspects in the production of ripe mango to eat are: maturity at harvest, requirement or not of hydrothermal quarantine treatment (HQT), temperature and duration of refrigerated transport, as well as handling during commercialization. The work was carried out in an area with and without the presence of fruit flies, as well as with and without requirement of HQT (Nayarit and northern Sinaloa, respectively). States of maturity at harvest (mature and ¾ fruit), refrigeration temperatures (12, 15, 18 and 22 °C), with or without HQT were evaluated. The variables analyzed were weight loss, pulp color, pulp firmness, total soluble solids (TSS), titratable acidity and °Bx/acidity ratio. It was found that the degree of maturity at harvest was not so impactful in most of the variables, while the temperature of transport had a significant impact on most of them. At lower temperatures, greater firmness, lower weight loss and slow development of TSS, as well as longer shelf life. The temperature of 12 °C showed measurements similar to 15 and 18 °C at consumption in all the variables evaluated, in addition to being the temperature with the highest shelf life. HQT led to up to two days less shelf life compared to fruits without HQT.